What Inhibits Manufactured Exports in Sub-Saharan Africa: Firm Level Evidence? - Kanayo, Ogujiuba; Nancy, Stiegler; Uzochukwu, Amakom (Mediterranean Journal of Social Sciences, 2012)
The poor performance of many less developed and developing countries including African economies have beenattributed to low growth of exports in general and manufactured exports in particular. In trying to remedy the situation, Sub-Saharan Africa (SSA) economies including Nigeria have adopted different strategies to woo foreign investors in the form offoreign direct investment (FDI) due to insufficient domestic investment that can propel the economic growth process.This studyattempts to investigate constraints to manufactured export using firm level evidence from seven SSA economies (Kenya,Nigeria, Tanzania, Cameroon, Mauritius, and South Africa). Employing probit regression and ordinary least squares (OLS), thestudy found that output per labour, raw materials per labour and indirect cost were the major constraints to manufacturedexports. Also, high production and transaction costs (indirect costs) were found to constitute the constraints for exporting both inSSA at large. Based on findings, there is need for provision of export incentives, which may come in two parts: measuresdesigned to increase firm-level efficiency as this would help firms to attain certain level of international competitivenessnecessary for sustainable exporting; and measures designed to reduce the transaction and production costs associated withexporting.